Kode Etik Profesi Notaris dalam Pelanggaran Pembuatan Akta Kepemilikan Saham - Dwityas Witarti Rabawati; Allesandro Patricio Quinaldy Ragat; Maria Fatima Kartika Mao Foju (Student Scientific Creativity Journal, 2024)
As long as a particular authentic deed cannot be made by another public official, the Notary is the public official who has the power to create it.. If a Notary ignores the honor and dignity of his position, violates general regulations, or makes other mistakes in carrying out his duties as a Notary, then supervision of the Notary is very important. So that this profession does not get bad marks from the public, as in the case that occurred on September 2 2022, a Notary named Oktaviana who acted carelessly in accepting the deed of shareholder decision statement whose contents could be detrimental to one of the parties. Apart from that, Notary Oktoviana is also suspected of siding with one of the parties so that he carried out the request to make deed number 6 dated 24 August and 13 September 2022 which resulted in huge losses for the other party.